Pencarian nomor telepon pada akun google dengan implementasi algortima pencarian linear - Mushoharoin, Achmad Michael (Maliki Interdisciplinary Journal, 2024)
The rapid development of technology and information today has many impacts, one of which is that humans can communicate remotely. This is supported because of the internet, where to communicate must use an intermediary using a telephone number. When someone has a lot of contact lists containing names and phone numbers stored in a google account, it will automatically be difficult for that person to search manually. This research aims to make it easier for users when they want to find data from a large set of data. In this research using linear search algorithm method to solve the problem. The result of this research is that the linear search algorithm is an efficient algorithm to be implemented in searching contacts in a google account. The linear search algorithm is an easy solution to search the list, because this method will iterate one by one the data in a set of data until there is data that matches the data being searched or until all data has been iterated.